2020
DOI: 10.7759/cureus.11099
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Ruptured Perineal Epidermal Cyst

Abstract: Epidermal cysts are common skin lesions. They are usually seen in the chronic sun-exposed areas of the skin. They can get complicated by inflammation, infection, rupture, or malignancy. Epidermal cyst in the perineal region is rare. We report a case of an infected ruptured perineal epidermal cyst mimicking gluteal abscess. The patient was successfully treated by complete surgical excision. Histology revealed epidermal cyst with foreign body giant cell reaction and no evidence of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…They are commonly distributed all over the body but uncommonly reported in the perineum [ 1 ]. Risk factors include exposure to ultraviolet rays, human papilloma virus infection, smoking and trauma [ 4 ]. Specific risk factors for perineal epidermoid cyst include mechanical pressure, perineal surgery, needle biopsies and minor trauma on the perineal area [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are commonly distributed all over the body but uncommonly reported in the perineum [ 1 ]. Risk factors include exposure to ultraviolet rays, human papilloma virus infection, smoking and trauma [ 4 ]. Specific risk factors for perineal epidermoid cyst include mechanical pressure, perineal surgery, needle biopsies and minor trauma on the perineal area [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of cyst is usually seen in the chronic sun-exposed areas of the skin including the face, neck or trunk with perineal and extremity locations being rare [ 1 , 4 ]. The prevalence is twice as common in males compared with females and can be diagnosed at any age but more commonly seen in the third and fourth decades of life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are caused by progressive cystic expansion and destruction of the funnels of hair follicles. For example, for some patients who undergo surgery other diseases, postoperative epidermoid cysts are formed in the surgical area due to the implantation of epidermal fragments into the dermis by penetrating injuries ( 12 , 13 ). (II) Some studies suggest that HPV(human papillomavirus) infection may be associated with the paroxysm of epidermal cysts, especially HPV types 57 and 60 ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, malignant transformations of giant epidermoid cysts of the abdominal wall are rare. A number of experts believe that some patients with epidermoid cysts have sustained irritation to the tissue at the cyst wall incision due to the epidermoid cyst contents postoperatively, resulting in chronic inflammatory responses that dephosphorylate the thin layer of the squamous epithelium, eventually leading to a malignant transformation of the epidermoid cyst and a formation of squamous carcinoma ( 12 , 23 ). In this case, the patient had previously undergone (incision) drainage of the epidermoid cyst in the abdominal wall, after which the cystic contents irritated the cystic wall at the incision for a prolonged period, which could be have caused the malignant transformation of the epidermoid cystic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal cyst is a common skin disease that can be complicated by infection, rupture, calcification and malignancy. 16,17 Shah et al showed that in 20 cases of scrotal calcinosis, the etiology was traced to epidermoid cysts in 14 cases. 17 Chronic and repeated irritation, infection, ultraviolet radiation, and immunosuppression may become the triggers of epidermoid cyst malignancy.…”
mentioning
confidence: 99%